2022
DOI: 10.1002/ijgo.14434
|View full text |Cite
|
Sign up to set email alerts
|

Chronic endometritis positively correlates with the aggravation of intrauterine adhesions but has limited effects on reproductive prognosis with antibiotic application

Abstract: Objective To assess the effect of chronic endometritis (CE) diagnosed by CD138 staining on the aggravation of intrauterine adhesions (IUAs), and the reproductive prognosis after transcervical resection of adhesions (TCRA). Methods Sixty‐three patients with severe IUAs (group A) and 119 patients with moderate IUAs (group B) were included in this retrospective study. TCRA and endometrial biopsy with CD138 staining were performed. Participants in each group were classified into two subgroups: CE group and NCE gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The possible mechanism is that the mechanical injury to the endometrium can basically remove the basal layer of the endometrium, followed by the immediate placement of LPS cotton threads, which on the one hand inhibits the endometrial regeneration, and on the other hand, LPS, which is the main component of the outer membrane of Gram-negative bacteria, induces the inflammatory response that leads to increased interstitial fiber activity and promotes the formation of IUA. In addition, using LPS alone can result in endometritis and it has been shown that chronic endometritis has a positive correlation with the aggravation of IUA [67]. Notably, considering that trauma and infection are the leading clinical causes of IUA, the dual damage is closer to the clinic-pathological characteristics of IUA than the 95% ethanol injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanism is that the mechanical injury to the endometrium can basically remove the basal layer of the endometrium, followed by the immediate placement of LPS cotton threads, which on the one hand inhibits the endometrial regeneration, and on the other hand, LPS, which is the main component of the outer membrane of Gram-negative bacteria, induces the inflammatory response that leads to increased interstitial fiber activity and promotes the formation of IUA. In addition, using LPS alone can result in endometritis and it has been shown that chronic endometritis has a positive correlation with the aggravation of IUA [67]. Notably, considering that trauma and infection are the leading clinical causes of IUA, the dual damage is closer to the clinic-pathological characteristics of IUA than the 95% ethanol injury.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, this inhibits endometrial regeneration, whereas on the other hand, it results in an inflammatory response to the main component of the outer membrane of Gram-negative bacteria that leads to increased interstitial fiber activity and promotes the formation of IUA. In addition, the use of LPS alone can result in endometritis, and it has been shown that chronic endometritis is positively correlated with the aggravation of IUA [ 63 ]. Notably, considering that trauma and infection are the leading clinical causes of IUA, the dual injury damage is closer to the clinicpathological characteristics of IUA than the 95% ethanol injury.…”
Section: Discussionmentioning
confidence: 99%
“…The cure rate of histopathologic CE following hysteroscopic surgery without antibiotic treatment in women with endometrial polyps, submucosal uterine fibroids, intrauterine adhesions, and septate uterus was 89.7%, 100%, 92.8%, and 83.3%, respectively. Xiang et al [ 95 ] confirmed a high prevalence of histopathologic CE in infertile women with severe intrauterine adhesions than in women with moderate ones (28.6% versus 15.1%). Following combined therapy of hysteroscopic resection of the lesions and single 14-day oral antibiotic treatment, the OPR and MR in these women in subsequent ET cycles were comparable to those in women without CE.…”
Section: Challenges In Clinical Management Of Cementioning
confidence: 99%
“…Intrauterine abnormalities have been identified as potential risk factors that can increase the risk of CE in infertile women. Several studies have demonstrated an association between specific intrauterine abnormalities and an increased likelihood of being diagnosed with CE (Xiang et al, 2023;Liu et al, 2019). However, the previous findings are controversial in this regard.…”
Section: Introductionmentioning
confidence: 99%